Measurement of Social Capital among Clinical Research Trainees. Issue 1 (3rd October 2013) - Primack, Brian A.; Colditz, Jason B.; Cohen, Elan; Switzer, Galen E.; Robinson, Georgeanna F.W.B.; Seltzer, Deborah L.; Rubio, Doris M.; Kapoor, Wishwa N.
Abstract While physical and human capital are established as important predictors of success among early‐career clinical investigators, less is known about the role of social capital. The authors aimed to develop a brief scale to assess social capital in this population and test its reliability and validity. A three‐item assessment was developed based on a conceptual framework and measures of social capital from other fields and was administered to 414 clinical research trainees at the University of Pittsburgh in 2007–2012. The measure exhibited good internal consistency reliability (α = 0.71) and a normal distribution. On a 10‐point scale, mean social capital was 6.4 (SD = 1.7). Social capital was significantly associated with 7 of the 9 expected constructs: sex, age, confidence in research skills, work‐related motivation, burnout, and social support. Exploratory multivariable regression analysis demonstrated that social capital was most strongly associated with higher research confidence (β = 0.35, p < 0.001), higher extrinsic motivation (β = 0.50, p = 0.003), and lower burnout (ptrend = 0.02). This three‐item scale measures social capital in this population with adequate internal consistency reliability, face validity, and construct validity. This brief assessment provides a tool that may be valuable to benchmark social capital of clinical research trainees and to better contextualize programmatic and trainee outcomes.